Consequences of Implementing Artificial Intelligence in Human Resource Management of Iranian Government Organizations - Rahdarpour, Javad; Okati, Hamid; Ostovar, Mostafa (AI and Tech in Behavioral and Social Sciences, 2025)
The present study aimed to examine the consequences of implementing artificial intelligence in human resource management within Iranian government organizations. The research method, in terms of data type, is mixed-method (qualitative-quantitative); in terms of the research environment, it is library-based; and in terms of data collection method, nature, and research method, it is descriptive-correlational. In this research, interviews were used to identify the consequences. The statistical population in the qualitative section consisted of 5 experts from Iranian government organizations, and in the quantitative section, 335 employees from these organizations. The data collection tool in the qualitative section was interviews, while in the quantitative section, a researcher-made questionnaire based on a five-point Likert scale was used. For data analysis in the quantitative section, Cronbach's alpha tests, Average Variance Extracted (AVE), the AVE square root matrix, and confirmatory factor analysis using smartPLS software were employed. The results showed that the consequences of implementing artificial intelligence in human resource management in Iranian government organizations span five areas: recruitment, training, performance evaluation, compensation, and retention. Moreover, the results indicated that among the components, the recruitment component requires further strengthening.